Stock Market Development and Economic Growth: A Comparative Evidence from two Emerging Economies in Africa – Nigeria and South Africa - Charity Ifunanya Osakwe; Amalachukwu Chijindu Ananwude (Archives of Current Research International, 2017)
This study empirically explored the short run and long run relationship between stock market development and economic growth by comparing two leading emerging economies in Africa: Nigeria and South Africa from 1981 to 2015. Growth rate of gross domestic product was used to measure economic growth, while stock market development was surrogated by market capitalization ratio to gross domestic product and stock value traded ratio. Data were carefully sourced from World Bank development indicators of both countries. The ARDL co-integration divulged equilibrium long run relationship between stock market development and economic growth in Nigeria but not for South Africa. In both short and long run, there was a positive but insignificant relationship between stock market development and economic growth in Nigeria and South Africa. The granger causality analysis deduced that economic growth of South Africa is significantly affected by market capitalization but not so in Nigeria. The variation in economic growth owing to fluctuation in stock market development indices were observed to be insignificant for both Nigeria and South Africa. The study concluded that stock market development is relevant to economic growth as postulated in theoretical literature. Information disclosure in the stock markets of both countries need to be improve upon in an attempt to reducing information asymmetries. The availability of vital information of listed firms to insiders in the market hinders foreign investments. The non-availability of rating agencies and of a well-defined structure of regulation handicap investors from adequate assessment of firms’ risk priori to investing their funds.